2023
DOI: 10.7759/cureus.42383
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Examination Maneuvers for Carpal Tunnel Syndrome: A Meta-Analysis

Abstract: Our purpose was to assess the diagnostic validity (sensitivity (Sn) and specificity (Sp)) of physical examination maneuvers for carpal tunnel syndrome (CTS). This meta-analysis utilized the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. Studies assessing exam maneuvers (including components of the CTS-6) for CTS were identified in MEDLINE (Medical Literature Analysis and Retrieval System Online) and Embase (Excerpta Medica Database) databases. Assessed maneuvers assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Zhang et al [26] reported a sensitivity and specificity of 47% and 56% for Tinel's test and 50% and 33% for Phalen's test, respectively. A meta-analysis by Ozdag et al [27] revealed median sensitivity and specificity for Tinel's sign as 59% and 80% and for Phalen's sign as 70% and 80%, respectively. These findings highlight considerable variability in sensitivity and specificity among tests for CTS in various studies and prior literature.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [26] reported a sensitivity and specificity of 47% and 56% for Tinel's test and 50% and 33% for Phalen's test, respectively. A meta-analysis by Ozdag et al [27] revealed median sensitivity and specificity for Tinel's sign as 59% and 80% and for Phalen's sign as 70% and 80%, respectively. These findings highlight considerable variability in sensitivity and specificity among tests for CTS in various studies and prior literature.…”
Section: Discussionmentioning
confidence: 99%
“…The SCT is still novel in its use for diagnosing compression neuropathy; however, the SCT faces criticism, given its history of variable reliability and accuracy in published reports. 5,[34][35][36] This review seeks to evaluate the diagnostic utility and applicability of the SCT by assessing the current literature and providing an updated report regarding its clinical utility, physiologic mechanism, and anatomic locations for use.…”
Section: Discussionmentioning
confidence: 99%